Learning Accessibility during the COVID-19 Era: An Overview - Baral, Raj K. (The Spectrum, 2023)
As face-to-face teaching-learning modality was not both feasible and adequate to continue the learning process during COVID-19, instructors resorted to flexible distant learning options. They used digital as well as print-based multimodal texts to ease teaching-learning activities and minimize learning loss during the period. The use of flexible modes of teaching like Universal Design (UD), multimodality, closed captioning on video programs, accessible assessment, and ways of using chat boxes for additional and meta-conversation helped address problems of dis/ability in both desperate and/or more normal times. This article reviews the attempts to ensure learning accessibility, and basically draws on secondary resources and data, to extract the relevant data and information to support its claim. The article concludes that, though it was a compulsion, as a lesson of the COVID-19 pandemic, instructors and learners learned ways to cope with challenging times in academia. Their knowledge on utilizing new tools and strategies helped minimize the gaps exacerbated by the pandemic in issues like equity, access, and engagement and will be a valuable lesson for any possible hard times in the future.